Water Governance, Stakeholder Engagement, and Sustainable Water Resources Management - Susanna Eden; Eylon Shamir; Sharon B. Megdal (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Water will focus on the relationship of water governance practices and stakeholder engagement approaches to the development, evaluation, and adoption of solutions to water management challenges. It is well recognized that the human dimensions of considering alternative water management scenarios and policy options are as least as important as their engineering, hydrological, and financial aspects. Identifying good governance practices and successful stakeholder engagement approaches can assist decision makers and water managers as they grapple with meeting the multiple environmental, economic, and societal objectives associated with sustainable water management. Papers are solicited that connect governance and/or stakeholder engagement approaches to the identification, characterization, and/or adoption of sustainable water management strategies, including conservation focused, flood risk reduction and technological solutions. The Guest Editors will consider papers addressing water governance and stakeholder engagement at all geographic scales, including transboundary. Papers addressing surface water, groundwater, and/or integrated water resources management are of interest, as are papers that examine indicators for governance and stakeholder engagement practices.